Filling in the Resource Gap of Urban Regime Analysis to Make It Travel in Time and Space. Issue 5 (September 2019) - Lambelet, Sébastien
Responding to recent studies that have argued that urban regime analysis (URA) is inappropriate for studying urban politics in Europe or in the twenty-first century, this article argues that URA is a powerful analytical tool to understand the dynamics of contemporary urban governance. It does so by drawing on evidence from the Swiss cities of Zurich and Bern since the turn of the millennium. In both cities, the realization of major urban projects has relied on strong public-private cooperation structured around the mobilization and exchange of five resources ("land, " "law, " "money, " "expertise, " and "democratic support"). Drawing on this empirical evidence, the article concludes by presenting two types of regimes: the PRIVATE-public regime and the PUBLIC-private regime.